Formulation and In-Vitro Evaluation of Sustained Release Matrix Tablets of Domperidone - Thapa, Chhitij; Chaudhary, Roma (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION Domperidone is a unique compound with gastro kinetic and antiemetic effects. It is used in the management of disorder by impaired motility like gastroesophageal reflux (in some instances), gastroparesis, dyspepsia, heartburn, epigastric pain, nausea, vomiting, and colonic inertia. The sustained release system is a widely accepted approach for slow drug release over an extended period to address the challenges of conventional oral delivery, including dosing frequency, drug safety, and efficacy. The study aims to formulate a domperidone sustained release tablet and compare the dissolution rate with the marketed formulations. MATERIAL AND METHODS Sustained release matrix tablets of domperidone were prepared by wet granulation method using different polymers such as HPMC K4M, ethyl cellulose, Gum acacia. Pre-compression studies like angle of repose, bulk density, tapped density, Carr's index, and Hausner’s ratio, and post-compression studies like weight variation, thickness, hardness, friability, drug content, and in-vitro drug release were evaluated. RESULTS The release profile of domperidone sustained-release tablets was studied spectrophotometrically. The in-vitro dissolution study suggests the minimum %-cumulative drug release with 98.33% in F5. The %-cumulative drug release was maximum in F3 with 99.69%. The in-vitro drug release of all the formulations was non-significant compared to the marketed formulation (p<0.05), exhibiting the sustained-release property by all the formulations. CONCLUSION The pre-compression study concludes the better flow property of the granules of different formulations. The sustained release domperidone tablets were prepared successfully by the wet granulation method. The post-compression parameters of different formulations were within the acceptable range.